UNIT 4.68 Solid‐Phase Synthesis of Oligo‐ADP‐Ribose. Issue 1 (1st March 2016) - Kistemaker, Hans A.V.; Meeuwenoord, Nico J.; Overkleeft, Herman S.; van der Marel, Gijsbert A.; Filippov, Dmitri V.
Abstract : Solid‐phase methodology for synthesis of adenosine diphosphate ribose oligomers (ADPr‐oligomers) of defined length is described using an advanced 2‐ribosyl adenosine phosphoramidite building block that is prepared in solution via an expeditious and high‐yielding method. The methodology is based on phosphitylation of a phosphomonoester as the key condensation step in the solid‐phase protocol. As ADP‐ribosylation appears to be an important yet poorly understood post‐translational modification of proteins, the presented methodology for rapid synthesis of ADPr‐fragments of exactly defined length should be of interest for researchers in the field of structural biology and cell biology. © 2016 by John Wiley & Sons, Inc.